2015
DOI: 10.1155/2015/724359
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inflammatory Bowel Disease in Hospitalized Elderly Patients in a Large Central Canadian Health Region

Abstract: Treatment approaches in elderly patients were different than in younger IBD patients despite having disease sufficiently severe to require hospitalization. While less accurate in UC, a single ICD-10 IBD code was sufficient to identify elderly CD and UC hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…While International Classification of Disease codes have been used in other studies examining the relationship between cardiovascular disease and IBD, 17,18,21,27,28,30,42 the NIS does not contain personal identifiers, and thus we are unable to validate the ICD-9-CM diagnosis codes of individual patients using chart review. ICD-9-CM coding has demonstrated accuracy in IBD 47,48 and other studies of gastrointestinal disorders, 49 however this remains a concern in our population given mixed performance within studies of patients with IBD in the Veterans Affairs system. 50,51 There also exists the potential for underdiagnosis of other risk factors, particularly tobacco use and obesity.…”
Section: Discussionmentioning
confidence: 93%
“…While International Classification of Disease codes have been used in other studies examining the relationship between cardiovascular disease and IBD, 17,18,21,27,28,30,42 the NIS does not contain personal identifiers, and thus we are unable to validate the ICD-9-CM diagnosis codes of individual patients using chart review. ICD-9-CM coding has demonstrated accuracy in IBD 47,48 and other studies of gastrointestinal disorders, 49 however this remains a concern in our population given mixed performance within studies of patients with IBD in the Veterans Affairs system. 50,51 There also exists the potential for underdiagnosis of other risk factors, particularly tobacco use and obesity.…”
Section: Discussionmentioning
confidence: 93%
“…However, other studies using the same CCI have shown a wide range of comorbidity prevalence. In these studies, the prevalences ranged from less than one fifth to more than two thirds of the included patients with one or more comorbidities 12,23 …”
Section: Discussionmentioning
confidence: 99%
“…In evaluations of administrative databases of adults, a single ICD-10 code has been accurate in the identification of patients with UC and CD. 45 Additionally, the KID database allows for cross-sectional analyses only, and thus we were unable to evaluate or account for the potential that a single patient could be admitted multiple times during the course of the study period. Our inability to evaluate readmissions is a significant limitation, particularly given that those patients with the longest LOS are likely the same individuals who are most likely to be readmitted within 30 or 90 days of their index hospitalization.…”
Section: Discussionmentioning
confidence: 99%